2006
DOI: 10.1007/s00396-006-1472-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of silver-poly(acrylamide-co-methacrylic acid) composite microspheres with patterned surface structures

Abstract: Acrylamide (AM) and methacrylic acid (MAA) copolymer microgels were prepared by a reverse suspension polymerization technique. The microgels were used as templates for the preparation of silver-poly(acrylamide-co-methacrylic acid) [Ag-P(AM-co-MAA)] composite microspheres. The surface structures of the microspheres prepared in this way are characterized by zigzag-like structures. It was found that the composition of the microgels, the nature and dosage of surfactants, the quantity of the metal, and even the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…That being the case, the technique should be suitable to produce polymer particles with internal cavities. Surprisingly, our experiments showed that even the original reaction recipe by Xia et al [27] can produce hollow polymer microspheres (see Fig. 2a).…”
Section: Experimental Workmentioning
confidence: 84%
See 1 more Smart Citation
“…That being the case, the technique should be suitable to produce polymer particles with internal cavities. Surprisingly, our experiments showed that even the original reaction recipe by Xia et al [27] can produce hollow polymer microspheres (see Fig. 2a).…”
Section: Experimental Workmentioning
confidence: 84%
“…1 shows the recipes and reaction conditions used in our experimental study. Experiment A was adopted as a model recipe based on the work by Xia et al [27] who investigated the synthesis of cross-linked poly(AAM-co-MAA) microspheres as a template for the preparation of silver composites with patterned surfaces. In that article, the internal structure of the polymer particles was ignored, probably because of the underlying hypothesis that suspension polymerization yields "solid" polymer particles.…”
Section: Experimental Workmentioning
confidence: 99%
“…Actually, polymer microgels have also found uses in the preparation of inorganic-polymer composite microspheres with patterned surface structures [35][36][37][38][39][40][41]. It was demonstrated that the surface structures of the final composite microspheres can be manipulated by varying the reaction conditions of the inorganic precipitation and the interface structures between the template microgels and the continuous phase.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the surface structures of the final composite microspheres can be manipulated by varying the reaction conditions of the inorganic precipitation and the interface structures between the template microgels and the continuous phase. By employing this technique, various fancy composite microspheres, such as CuS-PNIPAM, Ag 2 S-PNIPAM, CuS-P(NIPAM-co-AA), CuS-P(NIPAM-co-MAA), Ag 2 S-P(NIPAM-co-MAA), ZnS-P(NIPAM-co-MAA), CdS-P(NIPAM-co-MAA), and Ag-P-(AM-co-MAA), where AA and MAA stand for acrylic acid and methacrylic acid, respectively, have been synthesized in our laboratory [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, our research group has proposed a novel polymeric microgel template method and we have successfully prepared various inorganic-polymer composite microspheres with peculiar surface structures, such as metal sulfide-polymer, metalpolymer, insoluble salt-polymer, and oxide-polymer composites [41][42][43][44][45][46][47][48][49][50]. It has been found that the surface structures of the composite microspheres may be tailored to some extent by varying the chemical composition of the polymer microgels and by modulating the amount and type of inorganic compound deposited.…”
Section: Introductionmentioning
confidence: 99%